State- and frequency-dependence in autonomic rebalance mediated by intradermal auricular electroacupuncture stimulation - Yang, Sen; Wu, Yu-Rui; Zhan, Zheng; Pan, Yan-Hong; Jiang, Jin-Feng (Frontiers in Neuroscience, 2024)
Background: Vagus nerve stimulation (VNS) improves diseases such as refractory epilepsy and treatment-resistant depression, likely by rebalancing the autonomic nervous system (ANS). Intradermal auricular electro-acupuncture stimulation (iaES) produces similar effects. The aim of this study was to determine the effects of different iaES frequencies on the parasympathetic and sympathetic divisions in different states of ANS imbalance.We measured heart rate variability (HRV) and heart rate (HR) of non-modeled (normal) rats with the treatment of various frequencies to determine the optimal iaES frequency. The optimized iaES frequency was then applied to ANS imbalance model rats to elucidate its effects. Results: 30 Hz and 100 Hz iaES clearly affected HRV and HR in normal rats. 30 Hz iaES increased HRV, and decreased HR. 100 Hz iaES decreased HRV, and increased HR. In sympathetic excited state rats, 30 Hz iaES increased HRV. 100 Hz iaES increased HRV, and decreased HR. In parasympathetic excited state rats, 30 Hz and 100Hz iaES decreased HRV. In sympathetic inhibited state rats, 30 Hz iaES decreased HRV, while 100 Hz iaES decreased HR. In parasympathetic inhibited rats, 30 Hz iaES decreased HR and 100 Hz iaES increased HRV. Conclusion: 30 Hz and 100 Hz iaES contribute to ANS rebalance by increasing vagal and sympathetic activity with different amplifications. The 30Hz iaES exhibited positive effects in all the imbalanced states. 100 Hz iaES suppressed the sympathetic arm in sympathetic excitation and sympathetic/parasympathetic inhibition and suppressed the vagal arm and promoted the sympathetic arm in parasympathetic excitation and normal states.